A simple and economic three-step process for producing highly purified Fab’ fragments directly from the egg yolk water-soluble fraction - González Viacava, Myriam Belén (2022)
Although mammals are still the main source of polyclonal antibodies production, the use of egg yolk immunoglobulins (IgY) is increasing, and thus improvement of its safety to reduce undesired reactions is needed. Removal of IgY constant domains by pepsin enzymatic treatment is expected to reduce potential adverse effects derived from the parenteral administration of these antibodies, while also increasing its distribution volume. Current Fab’ production requires the previous purification of IgY to be used as starting material. In this context, relevant economic benefits may be gained if initial IgY purification could be avoided, by using rawer starting materials. In this work, a three-step process for Fab’ production from crude egg yolk water-soluble fractions is described using scalable and simple low-cost technologies such as ultrafiltration and anion exchange chromatography. The overall process yield of 33% highly pure Fab’ from water-soluble fractions favorably compares to the manufacture of related medicinal products from mammalian antibodies, such as antivenoms.